Manajemen Perguruan Tinggi Dalam Meningkatkan mutu Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Muhammadiyah (IAIM) Bima, NTB: Studi implementasi good university governance - Sitti Fatimah Azzahra (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
This study aims to describe critically college management, higher education quality, and good university governance in Islamic Institute Muhammadiyah Bima to find answers to the problems concerning: (1) How is the description of College Management of Islamic Institute Muhammadiyah? (2) How are the efforts implemented to improve the Higher Education Quality? (3) What are the principles of Good University Governance for improving the quality of education? (4) What are the barriers and challenges of College Management to improve the quality of education?. The results showed that the college management, in the control of institution governance, refers to the management functions of planning, organizing, and monitoring as well as the principles of good university governance that include transparency, accountability, responsibility, independence, and justice. In general, the implementation of college management has been accomplished by the rules set by the college. The successes that have been achieved by Islamic Institute Muhammadiyah in the efforts of developing higher education quality, as well as the implementation principles of college management, are the following. (1)The implementation of the three duties of College, (2) Creating effective good management, (3) Upgrading the competence of lecturers, (4) Improving the quality of learning, (5) Increasing the academic atmosphere, (6) Embodiment of academic purposes. There are also several factors inhibiting Islamic Institute Muhammadiyah Bima in the implementation. These are internal and external barriers.